Tantangan dan Masalah dalam Penerjemahan Kuesioner - Dewi, Haru Deliana (Jurnal Penerjemahan, 2020)
Questionnaire translation seems simple and easy. However, it turns out that the theory of questionnaire translation has evolved since 1970s where the scholars in the fields of medicine, psychology, and business or management have put their efforts to develop the ways and phases of questionnaire translation to obtain a successful and valid result. This study aims to present the challenges and problems in questionnaire translation from the opinions of those scholars and from the analysis of the English to Indonesian questionnaire translation samples. This paper applies library research and uses a qualitative approach to describe and analyze those challenges and problems. The result shows that there are two main problems in the translation of this text type, namely being too literal (faithful) translation and ethnocentricity. It is concluded that a questionnaire should not be translated closely to the source text and attention must be paid to the English culture carried out to the target text. Keywords: questionnaire translation; challenges and problems; being too literal; ethnocentricity.